Megawati Soekarno Putri Government Policy In Dealing With The Effects Of The Bali Bombings I In 2002 - David Hidayah; Marjono Marjono; Sumardi Sumardi; Nurul Umamah; Riza Afita Surya (JURNAL HISTORICA, 2022)
The Bali Bombing I in 2002 was one of the events caused by terrorists in Indonesia. Terror acts carried out in the Bali region with bombings killed 202 people. The incident occurred when the Indonesian government did not yet have laws and regulations governing the handling of explosions. The Bali Bombing I had a wide impact on the world of Bali tourism. The explosion destroyed the Paddy's Pub cafe, Sari Club and the United States Consulate. More than 519people were recorded, consisting of 202 people died and 317 people were outpatient. The Bali Bombing I caused many problems that had to be handled by the Megawati Soekarnoputri Government, among others, the obstacles to assistance from the central government to the Bali local government, the handling of legislation did not yet exist, limited hospital installations, reconstruction and normalization in the tourism sector had not yet been implemented. recovered for tourism promotion. Keywords: Government, Handling, Bali bomb I.